Economic Growth and Environmental Degradation in Oman: Testing the Environmental Kuznets Curve Hypothesis Using Time Series Analysis - Al-Hajri, Shamsa Salim; Khudari, Mohammed (International Journal of Energy Economics and Policy, 2026)
This study investigates the validity of the Environmental Kuznets Curve (EKC) hypothesis in Oman, examining the relationship between economic growth and CO2 emissions from 1998 to 2022. Using annual time series data, the study employs unit root tests, vector autoregressive (VAR) models, and Granger causality tests to analyze the dynamics between GDP per capita and environmental degradation. The results reveal that Oman is situated on the upward slope of the EKC, indicating a positive correlation between income levels and CO2 emissions. Both the quadratic and cubic EKC models demonstrate a strong goodness of fit, with the cubic model providing a more nuanced understanding of the non-linear relationship. The Granger causality tests confirm unidirectional causality from economic growth to emissions, while impulse response analysis suggests that Oman has not yet reached the turning point where environmental degradation begins to decline. These findings align with previous research on developing economies, highlighting the challenges of balancing economic growth with environmental sustainability. The study concludes that proactive policy measures, such as investments in renewable energy and stricter environmental regulations, are essential for Oman to transition toward sustainable development. The implications of this research extend to policymakers and stakeholders, emphasizing the need for integrated strategies to achieve the goals of Oman’s Vision 2040 while addressing global climate change challenges.